Ethical Investigation of Material Possession Among Contemporary Christians in Nigeria - Odeleye , Abraham Olutoye (International Journal of Culture and Religious Studies, 2023)
Purpose: God created material possession for sustenance of man on earth. Material possessions are indispensable in life and living a purposeful life requires having basic material possessions. The paper investigated Material Possession, Challenges of Material Possession and ethical response to the challenges of material possession among contemporary Christians in Nigeria. Methodology: The work is descriptive in nature and author employs a qualitative research approach that involves a combination of literature review and biblical analysis to address the subject of discussion. Material possession that some Christians at this contemporary time desire to acquire include latest vehicles, glamorous attire, attractive and solid houses, estates, clothes, electronic equipment and gadgets, plots of land, billions of dollars in their foreign accounts, productive firms at home and abroad and many of such. The greed of humans makes them pursue material possessions of the world at the expense of moral and spiritual values. Undue quest for material acquisition through bribery and corruption is detrimental to the moral and spiritual standard of Christian life. Findings: The paper identified compromise of some Christians, abuse of prosperity gospel, increase of social vices in the society, abandoned and inhabitable houses as challenges attached to material possessions among some Christians. The paper argues that acquiring material possession is not sinful, but undue means of material acquisition is against the will of God. Appropriation of Christian ethical response discussed in this paper is believed to promote biblical understanding of material possessions and godly ways of utilizing them to the glory of God and blessing of humanity. Unique Contribution to Theory, Policy and Practice : The study recommends that all Christians and responsible citizens should avoid every unethical way of acquiring material possession and learn to be contented in God. The true Church of Jesus Christ must uphold proactive teachings of the Bible on what constitutes true material possession. The article makes a notable contribution to the existing body o knowledge within Christian ethics, particularly in the context of expected biblical moral standard that should guide disposition of Christians to material possession.